Study of particle acceleration by magnetic reconnection in relativistic jets - Torrejón, Tania Elizabeth Medina (2021)
The ubiquitous relativistic jet phenomena associated with black holes play a major role in high and very-high-energy (VHE) astrophysics. In particular, observations indicate that blazars (active galactic nuclei with highly beamed relativistic jets pointing to the line of sight) show highly variable VHE emission, implying extremely compact emission regions. The real mechanism able to explain the particle acceleration process responsible for this emission is still debated, but magnetic reconnection has been lately discussed as a strong potential candidate. In this thesis, by means of three-dimensional special relativistic magnetohydrodinamical (3D-SRMHD) numerical simulations, we investigate the acceleration of test particles injected in a magnetized relativistic jet subject to current driven kink instability (CDKI), which drives turbulence and fast magnetic reconnection. We find that once the turbulence is fully developed in the jet, achieving a nearly stationary state, the amplitude of the excited wiggles along the jet spine also attains a maximum growth, causing the disruption of the magnetic field lines and the formation of several sites of fast reconnection. This occurs after the CDKI achieves a plateau in its non-linear growth. We performed a systematic search of magnetic reconnection sites in the evolved jet and obtained obtained average magnetic reconnection rates of ~ 0.05 (in units of the Alfvén speed) which are comparable to the predictions of the theory of turbulence-induced fast reconnection. Hundreds to thousands of protons injected in the nearly stationary snapshots of the jet, experience an exponential acceleration up to a maximum energy. For a background magnetic field of B ~ 0.1 G, this saturation energy is ~ 10^16 eV, while for B ~ 10 G é ~10^18 eV. The Larmor radius of the particles attaining the saturation energy corresponds to the size of the acceleration region, being of the order of the diameter of the perturbed jet. During this exponential acceleration, the velocity component of the particles that is predominantly accelerated is the parallel one to the local magnetic field. This regime of particle acceleration is very similar in all these evolved snapshots and lasts for several hundred hours until the saturation energy. The simulations reveal a clear association of the accelerated particles with the regions of fast reconnection, indicating its dominant role on the acceleration process. Beyond those saturation values, the particles suffer further acceleration to energies up to 100 times larger, but at a slower rate due to drift in the varying magnetic field. In the early stages of the development of the non-linear growth of CDKI in the jet, when there are still no sites of fast reconnection, injected particles are also efficiently accelerated, but by magnetic curvature drift in the wiggling jet spine. However, in order to particles to be accelerated by this process, they have to be injected with an initial energy much larger than that required for particles to accelerate in reconnection sites. Finally, we have also obtained from the simulations an acceleration time due to reconnection with a weak dependence on the particles energy E, tA E^ 0.1. The energy spectrum of the accelerated particles develops a high energy tail with a power law index p~ -1.2 in the beginning of the acceleration, in agreement with earlier works. Our results provide an appropriate multi-dimensional framework for exploring this process in real systems and explain their complex emission patterns, specially in the very high energy bands and the associated neutrino emission recently detected in some blazars.